Energy and exergy analysis of a new ejector enhanced auto-cascade refrigeration cycle. (15th November 2015) - Yan, Gang; Chen, Jiaheng; Yu, Jianlin
Highlights: A new ejector enhanced auto-cascade refrigeration cycle using R134a/R23 is proposed. The performance of new and basic cycles is compared by simulation method. The new cycle outperforms the basic cycle in both energetic and exergy aspects. Both cycles have optimum mixture compositions to obtain optimal performance. Abstract: A new ejector enhanced auto-cascade refrigeration cycle using R134a/R23 refrigerant mixture is proposed in this paper. In the new cycle, an ejector is used to recover part of the work that would otherwise be lost in the throttling processes. The performance comparison between the new cycle and a basic auto-cascade refrigeration cycle is carried out based on the first and second laws of thermodynamics. The simulation results show that both the coefficient of performance and exergy efficiency of the new cycle can be improved by 8.42–18.02% compared with those of the basic cycle at the same operation conditions as the ejector has achieved pressure lift ratios of 1.12–1.23. It is found that in the new cycle, the highest exergy destruction occurs in the compressor followed by the condenser, cascade condenser, expansion valve, ejector and evaporator. The effect of some main parameters on the cycle performance is further investigated. The results show that for the new cycle, the achieved performance improvement over the basic cycle is also dependent on the mixture composition and the vapor quality at the condenser outlet. The coefficient of performance improvement of the new cycle over the basic cycle degrades with increasing vapor quality. In addition, there exists an optimum mixture composition to obtain the maximum coefficient of performance for the new cycle when other operation conditions are given. The optimum mixture composition of both cycles may be fixed at about 0.5 under the given evaporating temperature.